The Uptake of SO 2 and NO 2 by Plants - Esguerra, Clementina; Santiago, Evangeline; Aquino, Nellie; Ramos, Mario (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Foliar removal of sulfur dioxide and nitrogen dioxide was measured in a closed exposure system. The purpose was to identify local plant species capable of removing appreciable amounts of these gases from the air. Seedlings of twenty-one plants were exposed to known concentrations of the pollutant. The difference in pollutant concentration before and after exposure period was taken as the amount absorbed by the plant.